The Increased Effect of Spring Leaf Unfolding on Autumn Senescence in the Northern and Southern Hemispheres - Dong Tang; Shubin Xie; Jie Peng; Ying Sun; Abraham Allan Degen; Yuan Sun; Jiali Luo; Zifan Li; Yaning Kuang; Lixue Wei; Weigang Hu; Longwei Dong; et al. (Global Ecology and Biogeography, 2025)
Aim To investigate the contributions of vegetation growth carryover (VGC, defined as the effect of present states of vegetation growth on subsequent phenophases) and climatic factors to plant phenology, particularly start‐of‐season (SOS) and end‐of‐season (EOS), and how these contributions have evolved globally over the past four decades. Location Global, with a focus on the Northern Hemisphere (NH) and Southern Hemisphere (SH). Time Period 1963–2015 for ground observations, 1982–2022 for satellite NDVI data, and 1982–2022 for climate data (temperature, precipitation, radiation, and potential evapotranspiration). Major Taxa Studied Global vegetation, without specifying individual species. Methods We analysed two sets of satellite‐derived NDVI data, ground‐based phenological observations, and long‐term climate data (temperature, precipitation, radiation, and potential evapotranspiration). Statistical models quantified the contributions of climatic factors and VGC to phenology trends. Results Globally, advanced SOS was driven primarily by increasing temperature and radiation, while delayed EOS was attributed to rising temperature and the carryover effect of spring vegetation growth (VGC SOS ). VGC SOS was the dominant driver of EOS in the SH, whereas temperature played a larger role in the NH. Over the past four decades, the contribution of VGC SOS to EOS has increased significantly on a global scale. However, the SH experienced pronounced “warming and drying” trends, which weakened the relative contribution of VGC SOS to EOS compared to climate‐driven delays. Main Conclusions VGC SOS plays a substantial role in shaping EOS in both hemispheres, with its importance increasing over time. These findings improve our understanding of vegetation dynamics and offer valuable insights for predicting vegetation growth and carbon sequestration under future global warming scenarios.